The impact of interest rates on small businesses and local economies. - Zandamela, Horácio Lucas (My University, 1998)
Many debates have been waged about the effect of the interest rate ceilings on the provision of financial services to small businesses. It has been considered as one of the major constraints in small business access to capital and it is also considered a major inhibitor of small business development. The present study attempted to determine whether interest rate ceilings should be undertaken or not, and how in a South African socio-political context this would help small business development. Concomitantly, it was considered how the interest rates affect small businesses according different purposes, size and terms of loans. A case study method was used to pursue this research. The case study of Mamelodi Township (Pretoria) and Kildare/Jonkllanqa village (Mhala District - Northern Province) were undertaken. Open-ended interviews with borrowers and financial institutions (providers) were conducted. The result of the interviews was analysed and reinforced with an analysis of national and international secondary literature. One of the main findings of the research was that interest rates ceiling are necessary and substantial in helping small business development. It was established that interest rate ceilings have to be considered in a flexible manner, accordlng specific conditions of small business activity. It was also concluded that interest rate ceilings have to be a consequence of a regulatory framework which enables small business access to capital, and, thus, development of their local community. The result of the research likewise, has indicated that for small, short term, working capital loans, the impact of interest rates on borrowers is smaller than for larger, longer term borrowers. The effect of the circulation of resources in a community in the case of a lower level interest rates deserves more investigation but there are primary indications of some positive impact on.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management).
Keywords: Interest rates -- South Africa.; Small business -- Finance.; South Africa -- Economic conditions.